1999
DOI: 10.1063/1.124661
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of dielectric layers grown on Ge by low temperature vacuum ultraviolet-assisted oxidation

Abstract: The growth of thin dielectric layers on (100) Ge samples at temperatures lower than 450 °C by photoassisted oxidation with vacuum ultraviolet radiation emitted by a Xe silent discharge lamp has been investigated. The thickness of the grown layers increased with both the oxidation time and processing temperature. Fourier transform infrared spectroscopy and x-ray photoelectron spectroscopy (XPS) indicated that the layers are mainly stoichiometric GeO2. XPS investigations also indicated the presence of a several-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…6 cm was used in this study. The surface preparation was performed by chemical treatment and in situ treatment in the UHV apparatus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 cm was used in this study. The surface preparation was performed by chemical treatment and in situ treatment in the UHV apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…16 It is well known that core-level photoelectron spectroscopy is a powerful tool to give detailed information about the chemical environment and oxidation states of oxides at solid surfaces. [5][6][7][8][9][23][24][25][26][27] Schmeisser et al 28 and Kuhr and Ranke 29 reported Ge 3d core-level spectra for various oxygen exposures to a Ge(100) surface. Two chemically shifted components of Ge 3d, corresponding to Ge atoms with one or two oxygen ligands, were debated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gibbs free energy change for the formation of each oxide is as follows: namely, −⌬G͑700°C͒ in the reaction of Si +2O 2 → SiO 2 is 728.9 kJ/ mol, 9 which is larger than 482.3 kJ/ mol of Ge+ 2O 2 → GeO 2 . 10 Thus, the surface became Si deficient as the ICP-induced oxides were removed through the HF etching.…”
Section: Resultsmentioning
confidence: 99%
“…Novel processes have been investigated, i.e. sulphur passivation [42], high pressure thermal oxidation [53,54], vacuum ultraviolet-assisted oxidation [55], plasma oxidation [56,57], radical oxidation [58,59], direct neutral beam oxidation [60], plasma postoxidation [61], and thermal molecular oxidation [62].…”
Section: Gate Dielectricsmentioning
confidence: 99%